Coherent optical control of polarization with a critical metasurface - Kang, Ming (2015)
We present a mechanism by which a metamaterial surface, or metasurface, can act as an ideal phase-controlled rotatable linear polarizer. Using coupled-mode theory and the idea of coherent perfect absorption into auxiliary polarization channels, we show how the losses and near-field couplings on the metasurface can be balanced so that, with equal-power linearly polarized beams incident on each side, varying the relative phase rotates the polarization angles of the output beams while maintaining zero ellipticity. The system can be described by a non-Hermitian effective Hamiltonian which is parity-time (PT) symmetric, although there is no actual gain present; perfect polarization conversion occurs at the eigenfrequencies of this Hamiltonian, and the polarization rotating behavior occurs at the critical point of its PT-breaking transition.